1998
DOI: 10.1677/jme.0.0210073
|View full text |Cite
|
Sign up to set email alerts
|

Fetal rat lung epithelium has a functional growth hormone receptor coupled to tyrosine kinase activity and insulin-like growth factor binding protein-2 production

Abstract: Although growth hormone (GH) receptor (GHR) mRNA and protein are present in fetal tissues such as the lung, there is little evidence that GH mediates growth in the fetus. We have identified functional responses to GH in fetal rat lung epithelia and suggest a possible role for GHR in the developing lung. GHR mRNA in lung extracts was high before birth at day 16 of gestation (16f), decreased to low levels at day 22f but increased again after birth. At day 20f GHR mRNA levels were higher in lung than in liver, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Immunocytochemistry and in situ hybridization (ISH) have also localized GHR and GHR mRNA within fetal rat lung epithelial cells (Garcia-Aragon et al, 1992;Edmondson et al, 1995) and GHRs have also been identified by Western blotting in fetal (Walker et al, 1992) and adult (Frick et al, 1998) rat lungs. Batchelor et al (1998) also found that the GHR mRNA was present in the rat lung from ED16 -ED21, corresponding to part of the pseudoglandular, the canalicular, and part of the saccular stages of rat lung development, and found that it was 50% more abundant than in the liver, which is a recognized GH target site (Baumbach et al, 1989). Moreover, these authors showed that GH stimulation of the receptor-induced tyrosine kinase activity, indicating that the fetal rat lung GHR is functional.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Immunocytochemistry and in situ hybridization (ISH) have also localized GHR and GHR mRNA within fetal rat lung epithelial cells (Garcia-Aragon et al, 1992;Edmondson et al, 1995) and GHRs have also been identified by Western blotting in fetal (Walker et al, 1992) and adult (Frick et al, 1998) rat lungs. Batchelor et al (1998) also found that the GHR mRNA was present in the rat lung from ED16 -ED21, corresponding to part of the pseudoglandular, the canalicular, and part of the saccular stages of rat lung development, and found that it was 50% more abundant than in the liver, which is a recognized GH target site (Baumbach et al, 1989). Moreover, these authors showed that GH stimulation of the receptor-induced tyrosine kinase activity, indicating that the fetal rat lung GHR is functional.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas roles for lung GH in lung development are currently unknown, it may participate in its vascularization, as GH stimulates angiogenesis in other tissues (Struman et al, 1999;Corbacho et al, 2002). It may also participate in cellular differentiation (Sanders and Harvey, 2004) or regulate immune function within the lung (Batchelor et al, 1998;Waters et al, 1999;Allen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GH receptors (GHRs) are present in the lung (Tiong et al, 1989;Garcia-Aragon et al, 1992;Batchelor et al, 1998) and exogenous GH induces the production of superoxide (Edwards et al, 1992), increases the activity of NFB (Liu et al, 2002) and phosphorylase A (Jost et al, 1979), and stimulates the tyrosine phosphorylation of specific, but unidentified, proteins in lung epithelial cells (Batchelor et al, 1998). Pathological changes in pituitary GH secretion also result in changes in lung function, because large lungs (Bartlett, 1971), upper airflow obstruction (Trotman-Dick-only be responsive to GH in peripheral circulation, but to GH produced locally as well.…”
Section: Introductionmentioning
confidence: 99%